The constant and the Variable in US Foreign Policy - Al-Gharawi, Esraa Qassim Ghanim (Journal of Posthumanism, 2025)
A change in US administrations does not mean a change in the direction of its foreign policy. US goals are specific and consistent in light of a comprehensive strategy. A change in US administrations is simply a response to internal and external conditions. In addition to the strengths of the United States’ ability to compete with emerging international powers, this is what we found in the change in administration under President Joe Biden, a Democrat with an idealistic foreign policy orientation. This contrasts with the administration of Donald Trump, a Republican with a realistic orientation, who relied on the use of force in its economic form.